The longevity of academicians: Evidence from the Saxonian Academy of Sciences and Humanities in Leipzig - Maria Winkler-Dworak; Heiner Kaden (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2013)
This study addresses the mortality of the members of the Saxonian Academy of Sciences and Humanities in Leipzig. In fact, learned societies have been shown to present vanguard groups in the achievement of longevity. We use biographical records from the members of the Saxonian Academy of Sciences from 1846 to 2010 and compare their mortality to German life table estimates, where particularly attention is paid to the mortality differentials between eastern and western Germany. The Saxonian academicians show indeed a higher life expectancy at age 60 than the general German male population, where the gap has been widening since the 1950s. Comparing the life expectancy values for the Saxonian academicians to available estimates of various European learned societies yields a similar longevity, suggesting that the survival of the academicians is less determined by national mortality conditions but that academicians rather share a common health advantage.
Keywords: 300; longevity; academies of sciences; Germany